2019
DOI: 10.1111/apa.15066
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment during eye examination for retinopathy of prematurity screening: Skin conductance versus PIPP‐R

Abstract: Aim To assess changes in skin conductance during retinopathy of prematurity screening and to study the correlation between the skin conductance and a validated pain scale. Methods Prospective observational study. Fifty‐three eye examinations were performed in 32 preterm infant candidates for retinopathy of prematurity screening. Outcome measures were changes in Premature Infant Pain Profile‐Revised (PIPP‐R) scale and number of skin conductance fluctuations. Results There was a significant increase from baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…22 Avila-Alvarez et al recently studied SCM during ROP examination and noted a significant increase in both SCM and PIPP-R scores during the procedure, but without a correlation between PIPP-R scores and skin conduction. 15 PIPP-R scores and SCM were both highest during scleral indentation in the study by Avila-Alvarez et al, 15 which is in concordance with our study where N-PASS scores and SCM were highest mainly during WFDRI during which scleral indentation was used. Avila-Alvarez et al also state that the main advantages of SCM is its objectivity and the possibility of continuous monitoring.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…22 Avila-Alvarez et al recently studied SCM during ROP examination and noted a significant increase in both SCM and PIPP-R scores during the procedure, but without a correlation between PIPP-R scores and skin conduction. 15 PIPP-R scores and SCM were both highest during scleral indentation in the study by Avila-Alvarez et al, 15 which is in concordance with our study where N-PASS scores and SCM were highest mainly during WFDRI during which scleral indentation was used. Avila-Alvarez et al also state that the main advantages of SCM is its objectivity and the possibility of continuous monitoring.…”
Section: Discussionsupporting
confidence: 92%
“…Although results from SCM vary in the current literature 15,22,24 it still seems that the method is capable of evaluating pain during short term interventions. In our previous study on SCM during heel lancing, we found that SCM at baseline took a longer time to stabilize and was higher in infants with a GA of < 28 weeks than in infants with a GA of ≥ 28 + 0 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have carried out experiments, and even a scoping review that describes the validity of SC based on past research 4 and so, in this article, we find an overview of SC and its comparison with another pain scale. Recent studies have reported a significant relationship between SCM and Neonatal Infant Pain Scale (NIPS) 19,22,30 , Neonatal Facial Coding System (NFCS) 22,26 , Premature Infant Pain Profile-Revised (PIPP-R) 28 , Bernese Pain Scale for Neonates (BPSN) 17 , Comfort-b 15 , Prechtl Scale 17 , Newborn Individualized Developmental Care and Assessment Program (NIDCAP) 20,29 , Acute Pain in Newborn (APN) score 5 and crying time. However, there are variations of previous studies report related similarity of SCM with other physiological and behavioural pain tools.…”
Section: Sc and Other Pain Physiological And Behavioural Scalesmentioning
confidence: 99%
“…Schubach used the Varioprot B SC apparatus, Zimmerman used the Q Sensor SC, and Petterson used the Sensormedic SC apparatus. 7,[9][10][11][12][13][14] In this study, the PaIncare-UI SC apparatus was used. The first reason is because this tool hasn't been comparing with other measuring instruments yet.…”
Section: Introductionmentioning
confidence: 99%